Odpowiedź :
Odpowiedź:
1,2,3,4
[tex]( \frac{ 4 !}{2 ! * 2 !}[/tex] ) * 2 ! = 3 ! * 2 = 6*2 = 12
a) { 12,13,14,21,23,24,31,32,34, 41,42,43 }
b) A = { 12,13,14,21,23,24}
B = { 12, 24,32 }
C = { 24, 31, 32, 34, 41, 42, 43 }
c) A ∪ B = { 12,13,14,21,23,24,32 }
B ∩ C = { 24, 32 }
B ' = { 13,14,21,23,31,34,41,42,43}
z.2
N = 6² = 36
A = { (3,6),(4,5),(4,6), (5,4),(5,5),(5,6),(6,3),(6,4),(6,5),(6,6) }
n = 10
P( A) = n : N = [tex]\frac{10}{36}[/tex] = [tex]\frac{5}{18}[/tex]
============
B = { ( 1,3), ( 3,1),(2,3), (3,2),( 3,3), (3,4),(4,3),( 3,5),(5,3),( 3,6),(6,3),(6,6), (2,6),
(6,2),(3,6),(6,3),(4,6),(6,4), (5,6),(6,5) }
n = 20
P(B ) = [tex]\frac{20}{36}[/tex] = [tex]\frac{5}{9}[/tex]
=============
z.3
P(A) = 0,35 P( B') = 0,24 ⇒ P(B) = 1 - 0,24 = 0,76
P( A ∩ B) = 0,537
więc
P ( A ∪ B) = P(A) + P(B) - P(A ∩ B) = 0,35 + 0,76 - 0,537 =
= 1,11 - 0,537 = 0,573
===================
Szczegółowe wyjaśnienie: